SYSTEMATIC REVIEWS: BALIA LOCAL WISDOM AS A HEALTHY SOLUTION TO KAILI - Arwan Arwan; Pitriani Pitriani (Preventif: Jurnal Kesehatan Masyarakat, 2018)
Background and Objetive: A community which still performs a traditional ceremony called “Balia” can be found in Balaora Village, In South Sulawesi, Indonesia. Although modern health services already exist, the Balia is a tradition of To Kaili community in solving their health problem. Material and Method: The method used is a systematic review of literature, a procedure performed by collect of information from several related sources to study the topic, then cataloging and documentation. Results: As an example of social behavior, when they suffer a disease, they prefer to visit a shaman rather than a medical doctor or educated health professionals. Another fact is when the folks fail in curing their health problems by modern health services, they will back to the traditional method such as a shaman or traditional herbs. Balia ceremony had existed long time ago and it is believed to be beneficial to To Kaili. According to their belief, the Balia ceremony is able to cast out evils in the human body. In a performance of the Balia Dance, all the dancers and participants need to involve their soul and felling; the attention must be concentrated into the ceremony.. Conclusion: The tradition of Balia as ancestral belief is believed to avoid all kinds of calamities and healing media. Therefore, the community thinks that there is no harm to perform it. Therefore, the tradition of Balia must be preserved and kept as an alternative for health problem of To Kaili in this modern era.